ANALISIS YURIDIS TANGGUNG JAWAB WERDA NOTARIS TERHADAP AKTA YANG BATAL DEMI HUKUM SESUDAH BERAKHIRNYA MASA JABATANNYA - LIDYA CHRISTIN NATALIA RODEARNI SARAGIH (PREMISE LAW JURNAL, 2017)
A Notary is a public official who has the authority to make authentic deeds, as long as they are not specified made by other public officials. Since tenure (term of office) has its limitation, one day a Notary can retire. As a public official, he has the liability for the deeds he has made even though notarial protocol has been submitted or moved to the notarial protocol keeper as stipulated in Article 65 of the Notarial Act No. 2/2014 in conjunction with the Notarial Act No. 30/2004.The ambiguity of norms in these articles has raised the question about the task and authority of a Notary as a public official and how about the liability of a retired Notary for the deeds he has made, and the causes and the liabiity of a Notary for null and void deeds in his post-tenure.The objective of this research is to develop jurisprudence, especially in Notarial affairs, which is related to his understanding about his liability for null and void deeds in his post-tenure.The research used the theory of liability and primary and secondary legal materials.Keywords: Notary, Liability, Authentic Deed, Retired Notary, Null and Void